1974
DOI: 10.1039/p19740001911
|View full text |Cite
|
Sign up to set email alerts
|

Phenol oxidation. Part III. Synthesis of the benzylisoquinoline alkaloid cularine

Abstract: Cularine has been synthesised via phenolic coupling of 1.2.3.4-tetrahydro-I -(3-hydroxy-4-rnethoxbenzyl)-7methoxy-2-rnethyIisoquinolin-8-ol; the latter was prepared by a new variant of the Pomeranz-Fritsch synthesis which leads directly to isoquinolines in good yield, with introduction of the 1 -benzyl substituent by the Reissert method. Syntheses of open-chain phenolic bis-(2-phenylethy1)amine derivatives related to cularine are also described ; however, none of these could be oxidatively coupled to give cula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

1974
1974
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…In 1974, Jackson et al reported an oxidative intramolecular coupling of tetrahydrobenzylisoquinoline derivatives 93a in the presence of K 3 [Fe(CN) 6 ] to produce cularine 94a and isocularine 95a in 2.5%, and 5% yield, respectively. 70 The Instead, the synthesis of didehydronorcularine 97 was achieved by Rodrigues and Abramovitch using C 6 F 5 I(OCOCF 3 ) 2 , yielding the desired cyclic diaryl ether in 87%, together with traces of ortho-cyclised derivative 98 (Scheme 23). 72 The same team also reported the synthesis of cularines through the use of nitrenium ions (Scheme 24), generated in situ by acid-catalysed decomposition of the azide precursor 99.…”
Section: Scheme 21 Phenoxazine Formation 4 Seven-membered Rings: Culamentioning
confidence: 99%
See 1 more Smart Citation
“…In 1974, Jackson et al reported an oxidative intramolecular coupling of tetrahydrobenzylisoquinoline derivatives 93a in the presence of K 3 [Fe(CN) 6 ] to produce cularine 94a and isocularine 95a in 2.5%, and 5% yield, respectively. 70 The Instead, the synthesis of didehydronorcularine 97 was achieved by Rodrigues and Abramovitch using C 6 F 5 I(OCOCF 3 ) 2 , yielding the desired cyclic diaryl ether in 87%, together with traces of ortho-cyclised derivative 98 (Scheme 23). 72 The same team also reported the synthesis of cularines through the use of nitrenium ions (Scheme 24), generated in situ by acid-catalysed decomposition of the azide precursor 99.…”
Section: Scheme 21 Phenoxazine Formation 4 Seven-membered Rings: Culamentioning
confidence: 99%
“…method was improved by using an N-borane complex of 93b, treating it with VOF 3 to yield 94b in 56% yield (Scheme 22). 71 Scheme 22 Synthesis of cularines and isocularines with K 3 [Fe(CN) 6 ] 70 and VOF 3…”
Section: A Rossignon D Bonifazimentioning
confidence: 99%
“…Aristoyagonine (40) (+ )-Norcularicine (10) ( + )-Celtine (6) Norsecocularine (43) (+)-Celtisine (3) Noyaine (45) ( + )-Claviculine (22) Oxocompostelline (21) (+)-Culacorine (1) Oxocularine (20) ( + )-Cularicine (9) Oxosarcocapnidine (29) ( + )-Cularidine (5) Oxosarcocapnine (30) ( + )-Cularimine (8) Oxosarcophylline (28) ( + )-Cularine (7) (+ )-Sarcocapnidine (23) (±)-Dihydrolinaresine (37) (+)-Sarcocapnine ( 25) Gouregine (31) Secocularidine (41) (+ )-4-Hydroxysarcocapnine (27) Secocularine (42) (+ )-Limousamine (14) Yagonine (39) (±)-Linaresine (36) Alphabetical List of the Cancentrine Alkaloids and the Quettamines…”
Section: Alphabetical List Of the Cularine Alkaloidsmentioning
confidence: 99%
“…Mass spectral mass numbers are followed in parentheses by relative abundance of ions, when these have been reported in the original literature. Synthetic (3,4) 3-(+)-CELTISINE IR: (CHC13) 3560 (7) PMR: (CDC13) (7) See also (5) MS: 327 (M+, 100) (7) See also (5,8) Sources: Synthetic (5-10) 157°( Et2Q-MeOH) (4,12,16) (HC104) 297°(MeOH) (11) [a22D: +292°(c = 0.99, CHC13) (11, 18a) UV: 284 Fumariaceae: Corydalis claviculata (L.) DC. (11, 13) Dicentra cucullaria (L.) Bernh.…”
mentioning
confidence: 99%
“…[7] O ). [8] Ausgehend vom 6-Methyl-7-isochinolinol (21), welches nach Jackson [9] in einer 5stufigen Synthese in 80% Ausbeute ausgehend von m-Methoxytolualdehyd hergestellt wurde, konnte nach einer Methode von Tsizin [10] 22 in 50% Ausbeute gewonnen werden. Isochinolindion 31.…”
unclassified